2018
DOI: 10.1093/infdis/jiy595
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Avian Influenza A(H7N2) Virus Infection Among Animal Shelter Workers Using a Novel Serological Approach—New York City, 2016–2017

Abstract: Background.-In 2016, an influenza A(H7N2) virus outbreak occurred in cats in New York City's municipal animal shelters. One human infection was initially detected.Methods.-We conducted a serological survey using a novel approach to rule out cross-reactive antibodies to other seasonal influenza viruses to determine whether additional A(H7N2) human infections had occurred and to assess exposure risk.Results.-Of 121 shelter workers, one had serological evidence of A(H7N2) infection, corresponding to a seroprevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
1
28
0
1
Order By: Relevance
“…Serum adsorption reduced cross‐reactive binding antibodies and enhanced the difference between the MN ≥40 and MN <40 groups for samples from the A(H7N2) study. The results are consistent with our previous report, and exposed novel HA antigen can be determined more accurately after serum adsorption . On the other hand, no significant difference was achieved for samples from the A(H5N1) study, partly due to the selection of samples that showed either high cross‐reactivity in MFIs against H5.Indo.06 GH after 2‐Ads (>2000) and/or relatively high MN titer against A/duck/Bangladesh/1907/2013 (GMT 23, Table ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Serum adsorption reduced cross‐reactive binding antibodies and enhanced the difference between the MN ≥40 and MN <40 groups for samples from the A(H7N2) study. The results are consistent with our previous report, and exposed novel HA antigen can be determined more accurately after serum adsorption . On the other hand, no significant difference was achieved for samples from the A(H5N1) study, partly due to the selection of samples that showed either high cross‐reactivity in MFIs against H5.Indo.06 GH after 2‐Ads (>2000) and/or relatively high MN titer against A/duck/Bangladesh/1907/2013 (GMT 23, Table ).…”
Section: Resultssupporting
confidence: 91%
“…For example, the age‐related antibody baseline level to A(H1N1)pdm09 in recent years would be much higher than those reported in 2009, due to extensive exposure to A(H1N1)pdm09 virus through infection or vaccination post‐2009 . If we can determine whether low levels of age‐specific, subtype cross‐reactive antibodies are present in the population, single convalescent‐phase serum specimens may be sufficient to determine a recent exposure to novel subtype influenza …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations